Educational thought and ideology in modern Japan : - Horio, Teruhisa (University Tokyo Press, 2001)
This book to include 3 part, Part I: the intellectual legacy of Japan's educational history, Part: II education in the courtroom and teachers' struggles for professional autonomy and part III: individualism and egalitarianism in Japanese education.